D.B. Nichols scrapbooks - Nichols, D. B.
Scrapbooks containing correspondence and newspaper clippings pertaining chiefly to Nichols's Civil War service as superintendent of the Freedman's Village, Arlington County, Va., and to his involvement with the American Missionary Association and with Howard University, Washington, D.C. Also mentions his work with the Massachusetts Sabbath School Society promoting the Sabbath School in Illinois and Iowa. Subjects include the arrival of contrabands and freedmen; rations; supplies; requests for slaves or freedmen to work on construction projects and farms or as servants; and life in Washington, D.C., following the Civil War. Correspondents include Elias M. Greene and N.R. Collins.
Missionary, educator, and librarian. Full name: Danforth B. Nichols. Born, 1816. Died, 1906.
Collection material in English.
Keywords: Collins, N. R. -- Correspondence; Greene, Elias M. -- Correspondence; American Missionary Association; Howard University; Massachusetts Sabbath School Society; Freedmen -- United States; Freedmen -- Virginia; Sabbath schools -- Illinois; Sabbath schools -- Iowa; Sabbath schools -- Massachusetts; Slavery -- United States; Freedman's Village (Arlington County, Va.); United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Social life and customs; Educators; Librarians; Missionaries